PENILAIAN PERKEMBANGAN ANAK USIA DINI DI TK IT BAITUSSHALIHIN DAN TK IT PERMATA SUNNAH PADA MASA PANDEMI COVID-19 - Afri Rahmawati; Bahrun .; Rosmiati . (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2021)
Keywords: Developmental Assessment, Early Childhood Education, Covid-19 Assessment of child development is very important to be carried out by a teacher. Through assessment the teacher can find out how far the child has achieved the development that he must have. The teacher conducts a developmental assessment by making observations of each child's activities, including behavior, facial expressions, and other activities carried out by children using various assessment techniques. However, during the Covid-19 pandemic, learning was carried out from home, so that teachers had difficulty in assessing children's development. The study, entitled